2002
DOI: 10.1046/j.1472-8206.2002.00086.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of pharmacokinetic modelling to the routine therapeutic drug monitoring of anticancer drugs

Abstract: Over the last 10 years, proofs of the clinical interest of therapeutic drug monitoring (TDM) of certain anticancer drugs have been established. Numerous studies have shown that TDM is an efficient tool for controlling the toxicity of therapeutic drugs, and a few trials have even demonstrated that it can improve their efficacy. This article critically reviews TDM tools based on pharmacokinetic modelling of anticancer drugs. The administered dose of anticancer drugs is sometimes adjusted individually using eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 66 publications
1
42
0
Order By: Relevance
“…It has been suggested that TDM should be reserved for only a proportion of patients, depending on factors such as tumor type, anticancer drug, and patient characteristics [74]. However, despite its limitations, more and more research is being done on the use of TDM in oncology [73][74][75]. For example, Ratain et al [17] introduced a (complex) formula to dose etoposide based on pretreatment WBC, among others, whereas a populationbased Bayesian methodology to routinely adjust etoposide therapy when given as a 5-day infusion, based on its pharmacokinetic profile as determined on the first day, was proposed by others [76].…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
“…It has been suggested that TDM should be reserved for only a proportion of patients, depending on factors such as tumor type, anticancer drug, and patient characteristics [74]. However, despite its limitations, more and more research is being done on the use of TDM in oncology [73][74][75]. For example, Ratain et al [17] introduced a (complex) formula to dose etoposide based on pretreatment WBC, among others, whereas a populationbased Bayesian methodology to routinely adjust etoposide therapy when given as a 5-day infusion, based on its pharmacokinetic profile as determined on the first day, was proposed by others [76].…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
“…Of the many challenges, ensuring that optimal exposures of drug are achieved in tumor versus normal tissues is one of the most important (reviewed in refs. [1][2][3]. The field of pharmacokinetics, which is concerned with the absorption, distribution, metabolism, and excretion of drugs, is instrumental to the drug development process and is applied to both preclinical and clinical investigations.…”
Section: Introductionmentioning
confidence: 99%
“…The nonradioactive plasma data were convolved with the group average human PET temozolomide IRF to calculate tissue concentrations of the drug under different clinically used dosing schedules. The short elimination half-life of temozolomide ensures that there is minimal drug accumulation NOTE: VD (1) , K 1 , and MRT (mean residence time) were calculated using spectral analysis (12) and averaging over m slices from scans of n patients; VD (2) was calculated using the rank-shaped estimator (28). Tissue pharmacokinetic parameters derived with and without contribution of regional blood volume are presented.…”
mentioning
confidence: 99%
“…The serious adverse effects of anticancer drugs in the clinical setting are often mentioned in the literature. [3][4][5] Site-specific targeting of anticancer drugs to tumor tissues remain a major challenge in cancer chemotherapy. [5][6][7] To overcome these drawbacks, nanomaterials, nanoparticles, polymer-drug conjugates, and nanodevices have been extensively investigated in the last 2 decades.…”
Section: Introductionmentioning
confidence: 99%